Biphasic Calcium Phosphate Microparticles Mixed With Autologous Blood: Application for the Reconstruction of a Large Mandibular Bone Defect in a Dog. (December 2020) - Girard, Nicolas; Cauvin, Edouard R. J.; Gauthier, Olivier; Gault, Simon
Large mandibular bone defects can be difficult to treat in dogs, with a high risk of mal or nonunion due to instability and risk of infection. This case report describes the use of autologous clotted blood mixed with biphasic calcium phosphate microparticles to fill a defect in a nonunion fracture and promote bone regeneration in a dog using a 2-stage surgical approach. This new method was designed and tried in a dog with a chronic, unstable mandibular fracture associated with a large sequestrum. Initial treatment involved debridement of the lesion, then the oral wound and oral vestibule were reconstructed in 2 layers. Four weeks later a second stage surgery allowed placement of a pre-contoured maxillofacial plate to bridge the defect, which was filled with a blood/biphasic calcium phosphate compound implant. Cone-beam computed tomography was used prior to the initial surgery for preoperative planning and 3-D printing of a mandibular template for plate contouring. CT was subsequently used to document the healing process, using a bone density measurement tool to assess bone regeneration. Radiographic evidence suggestive of osseointegration was observed within 6 months with effective filling of the defect and restoration of alveolar ridge continuity. A return to normal and atraumatic occlusion was considered excellent. Cone-beam computed tomography was found useful to document radiographic evidence of osseointegration, bone regrowth and remodeling. This case report is to serve as a proof-of-concept study and should be followed by a prospective evaluation.